Electrocardiographic changes in rats with metabolic syndrome and type 2 diabetes mellitus - Yu. A. Filippov; A. V. Stepanov; A. O. Shpakov; K. V. Derkach; M. G. Dobretsov (Сибирский научный медицинский журнал, 2025)
Impaired cardiovascular function in metabolic syndrome (MS) and type 2 diabetes mellitus (T2DM) is not adequately studied, and data on changes in electrocardiogram (ECG) parameters, including in rodent models of MS and T2DM, are contradictory and ambiguous.   Aim of the study was to investigate ECG parameters in models of MS and T2DM and to identify possible correlations between impaired glucose tolerance and the severity of changes in ECG parameters.   Material and methods. Male Wistar rats were used in the experiments. MS was induced by a high-fat diet (HFD) for 17 weeks; T2DM was induced by a combination of HFD and streptozotocin injection (HFD + STZ): 11 weeks of HFD followed by an injection of streptozotocin and continued HFD for another 6 weeks. Control animals were kept on a standard diet.   Results. The glucose tolerance test confirmed the development of impaired glucose tolerance to the prediabetic level in the HFD group and to the diabetic level in the HFD+STZ group. ECG changes were found only in the HFD+STZ group: a significant (compared to the control and HFD group) increase in the amplitude and area T wave on the ECG was shown.   Conclusions. Pronounced ECG abnormalities develop only in the model of T2DM, but not in the MS model.